PERAN ORANGTUA DALAM MENUMBUHKAN MOTIVASI BELAJAR ANAK - Wahidin (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
This paper discusses the role of parents in improving children’slearning motivation. The children referred to in this paper are children ofprimary school age (SD / MI) ie those aged 6.0 years to 12 years. Parents have avery important role in the education of their children among them as a motivator.In this case the parents should always give encouragement to their children tohave a passion in learning, especially in home study as a supporter of successfulachievement in school. The efforts that can be done by parents in improvingmotivation to learn children include: 1) Knowing the results, 2) Providingrewards and punishments, 3) Provide the necessary tools or facilities. Parentsas educators should always pay attention to the child’s personal developmentas a determinant in the treatment of education in accordance with the period orlevel of age and ability to think child.